Square Wave Voltammetric Determination Of Lead In Commercial Kohl Using A Glassy Carbon Electrode - Saha, M. A.; Alia, M.; Rebiai, A.; Lanez, T. (University of Eloued جامعة الوادي, 2011)
A simple sensitive square wave voltammetric method for the determination of lead contamination of several kohl samples purchased from Algeria retail stores was developed using glassy carbon electrode. The peak current response of 5 standards aqueous solution of lead in NaNO3 as supporting electrolyte was observed showing a linear calibration curve in the concentration range of 4×10-3 – 2.5×10-4 mol/l of lead. Over this concentration range, the equation obtained from the linear calibration graph for lead is Y = 0.00068 + 0.0093x with a correlation coefficient of r2 = 0.987. Following this step, the potential of an aqueous solution of 12 kohl samples containing 2 M nitric acid solution as supporting electrolyte is then swept in the same range of potential (-400 to -700 mV). The amount of lead is then deduced using the linear calibration graph for lead. The results showed up to 52.14% of lead present in kohl, this concentration was over the safe limits of lead set by the world health organization standards. However; only five commercial samples of ko
Articale in Journal of fundamental and Applied Sciences Vol. 03 N. 02
Keywords: Square wave voltammetry, kohl, lead, surma.